2019
DOI: 10.1161/jaha.118.011696
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Status on Stroke Recurrence

Abstract: Background Smoking is a well‐established risk factor of stroke and smoking cessation has been recommended for stroke prevention; however, the impact of smoking status on stroke recurrence has not been well studied to date. Methods and Results Patients with first‐ever stroke were enrolled and followed in the NSRP (Nanjing Stroke Registry Program). Smoking status was assessed at baseline and reassessed at the first follow‐up. The primary end point was defined as fatal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 40 publications
5
64
1
Order By: Relevance
“…Lots of factors including oxidative stress, endothelial dysfunction, and inflammation by smoking aggravates atherosclerosis, as a consequence, stroke occurrence [20,21]. Moreover, Chen et al [22] lately reported that smoking increases the risk of stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of factors including oxidative stress, endothelial dysfunction, and inflammation by smoking aggravates atherosclerosis, as a consequence, stroke occurrence [20,21]. Moreover, Chen et al [22] lately reported that smoking increases the risk of stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke Primary prevention BP reduction [18][19][20][21] Yes Not smoking 22 Yes Heart healthy diet 23,24 Yes a Exercise 24,25 Yes Lipid-lowering medication 26 Yes a Antiplatelet medication 27 No Anticoagulation for A Fib 28 Yes Screening Carotid Doppler 29,30 No b Tertiary prevention BP reduction 31 Yes Not smoking 32 Yes Heart healthy diet 33 Yes Exercise 33 Yes Lipid-lowering medication [34][35][36] Yes Antiplatelet medication 37 Yes Anticoagulation for A Fib 28 Yes Coronary artery event Primary prevention BP reduction [18][19][20][21] Yes a Not smoking 38 Yes Heart healthy diet 39 Yes a Exercise 40 Yes a Lipid-lowering medication 26 Yes a Antiplatelet medication 27 No Screening…”
Section: Condition Type Of Prevention Intervention Recommendationmentioning
confidence: 99%
“…There is strong evidence that smokers who experience a stroke can substantially reduce their risk of a subsequent stroke by stopping smoking. 32 Though these data do not pertain specifically to older adults, it is advisable to recommend that older adults who have had a stroke and continue to smoke cigarettes should stop.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…As one key component of cardiovascular health metrics, smoking increases the risk of virtually all cardiovascular disease subtypes [34]. Smoking cessation had been demonstrated as a modifiable risk factor both for primary and secondary prevention of stroke [35][36][37]. However, the effect of single ideal CVH metrics maybe partly attributable to other lifestyle behavior changes (eg., the subject has more exercise and healthier diet at the same time with smoking cessation) [36,38].…”
Section: 2mentioning
confidence: 99%